Identifying Topics and Evolutionary Trends of Literature on Brain Metastases Using Latent Dirichlet Allocation - Chen, Jiarong; Williams, Matt; Huang, Yanming; Si, Shijing (Frontiers in Molecular Biosciences, 2022)
Research on brain metastases kept innovating. We aimed to illustrate what topics the research focused on and how it varied in different periods of all the studies on brain metastases with topic modelling. We used the latent Dirichlet allocation (LDA) model to analyse the titles and abstracts of 50176 articles on brain metastases retrieved from Web of Science, Embase and MEDLINE. We further stratified the articles to find out the topic trends of different periods. Our study identified that a rising number of studies on brain metastases were published in recent decades at a higher rate than all cancer articles. Overall, the major topics focused on treatment and histopathology. Radiotherapy took over the first and third places in the top 20 topics. Since the 2010s, increasing attention concerned about gene mutations. Targeted therapy was a popular topic of brain metastases research after 2020.